The effectivity of ethanolic extract of binahong leaves (anredera cordifolia (tenore) steen) gel in the management of diabetic wound healing in aloxan-induced rat models - Kintoko Kintoko; Astri Desmayanti (Faculty of Medicine, Universitas Islam Indonesia, 2016)
Background : Diabetes Mellitus (DM) is a disease that can be known by increasing a blood glucose level and caused many kinds of complications if it don't properly treatment, one of those complications is a diabetic ulcer. There are many types of treatments created to overcome the diabetic ulcer, but there are not effective yet. Therefore, ethanolic extract gel of binahong (Anredera cordifolia (Tenore) Steen) leaves is used to make a new innovation of diabetic ulcer treatment Objective : The objective of this research wasto know the concentration of antibacterial and anti-infection activity from ethanolic extract of binahong leaves as wound healing on diabetic ulcer and also to know the changeover of wound diameter. Methods : Binahong leaves were extracted with 96% ethanol by maceration. Then the extract was formulated to be gel product with the concentration of 10% and 30%. The gel product was administrated to diabetic rats which had been made ulcer wound by excision. The result of wound diameter and the percentage of wound healing were analyzed by One Way Anova and then continue analyzed by LSD (Least Significant Different) with significant level of 95%. Results : The result showed that binahong gel with concentration variation of 10% and 30% only affected the organoleptic and doesn't affect the homogeneity, pH, irritation, spreadability and consistency. The result of the effectiveness test of binahong leaves gel is 10% more effective to changeover of wound diameter but there is not significantlydifferent if compared with 30% gel of binahong leaves. Therefore, gel of binahong leavesof 10% is able to provide slightly effective than chloramphenicol™. Conclusion : The concentration of 10% and 30% of binahong gel were effectively usage for wound healing diabetic ulcer in rats.